十字轴万向节串联轴系扭转动力学分析 - 陈晓红; 董海军; 葛文杰; 柏龙 (Jixie chuandong)
Based on concentration mass method,torsion vibration equivalent model of shafting system with multiple cardan joints is established,as well as torsion vibration dynamical equations of shafting system are presented by considering the transmission efficiency of cardan joints and the damper of transmission shafts.Accordingly,the effect of the stiffness of intermediate shafts and the angle between shafts on the response of shafting system angular velocity,the transmission accuracy and the transmission ratio are analyzed.Finally,the effect of different stiffness of shafts on shafting system is analyzed by instance solution.It provides theoretical references for keeping the torsion vibration of shafting systems used in aeroplane under restraint in its design,and for reducing the mass of driveline.